(untitled) (Research, Society and Development, 2020)
This study characterizes fishery and socioeconomic aspects of recreational fishing anglers in the Maritime Recreational Fishing Pier in Mongaguá (São Paulo, Brazil). We interviewed 114 anglers average aged 51 (± 13.5) years, between December 2012 and August 2016. Group fishing lasted 8.2 (± 4.8) hours with a mean catch rate of 9.4 (± 11.8) fish/angler/day and 1.9 (± 3.5) kg/day/angler. The average annual catch rate of 30,120 (± 23,177) kg is equivalent to 46% of commercial fishing in the same municipality during the same period (65,145.9 ± 16,575.7kg). The most sought after species was Trichiurus lepturus (swordfish), although the most caught were the catfish (family Ariidae). We registered different combinations of techniques, devices, and baits for capturing species with different habitat preferences under the pier. Recreational fishing anglers pointed to problems related to infrastructure such as burnt-out lamps, lack of trash can along the pier and lack of painting of the walls, conflicts with commercial fishers and surfers, and the decreasing of size of fish caught. We recommend integrated management measures taking into account the social groups and activity sustainability.